Insights from Madrosatul Alsun: A Communicative Vocabulary Learning in Non-Formal Education | Nadzaraat min Madrasah Alsun: Ta'liim Al-Mufradaat Al-Ittishaaliy fiy Ta'liim Ghair Al-Rasmiyy - Muhammad Thohir; Mochammad Indra Yumanto (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2023)
The use of communicative context, repetition, visual associations, and accurate pronunciation are essential elements contributing to Arabic vocabulary learning. This study investigates how communicative vocabulary learning and its contributing elements are implemented at Madrosatul Alsun in the context of non-formal education. The research method used is a qualitative approach with a case study. Data was collected through in-depth interviews, participant observation in the classroom, and documentation. The obtained data is qualitatively analyzed in three phases: first, through condensation involving data selection, purification, simplification, summarization, and transformation; second, through data display to facilitate understanding of the issues; and third, drawing conclusions, where data interpretation is performed. The results indicate that vocabulary learning is conducted by integrating it with other skills, using various techniques, including direct conjugation, definitions, synonyms, antonyms, and visual references, and translating only under specific conditions. The discussion of these findings provides new insights into the model of "meaningful words in meaningful learning," a pattern of vocabulary learning within a communicative approach in a course classroom context distinct from the formal education classroom context.